2012
DOI: 10.1002/art.33451
|View full text |Cite
|
Sign up to set email alerts
|

Editorial: Osteoarthritis as an autoinflammatory disease caused by chondrocyte‐mediated inflammatory responses

Abstract: We report on craniomicromelic syndrome in a male fetus. This case had the previously reported features of prenatal onset growth retardation, underossified cranial bones, wide sutures and fontanels, small face as compared to head, small palpebral fissures, pinched nose, microstomia, micrognathia, and narrow thorax. The consistent combination of these features with short appearing limbs as observed in this case establishes this syndrome as a distinct entity. © 2011 Wiley‐Liss, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
57
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 11 publications
1
57
0
Order By: Relevance
“…The characteristic features of OA include knee joint edema, decomposition of cartilage, hyperplasia of synovium and degradation of sub-chondral bones [16]. Various cytokines such as nitric oxide, PG, interleukin-1β, tumor necrosis factor-α, interleukin-6 and interleukin-8 are expressed in higher proportions in the chondrocytes of OA patients [6,9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The characteristic features of OA include knee joint edema, decomposition of cartilage, hyperplasia of synovium and degradation of sub-chondral bones [16]. Various cytokines such as nitric oxide, PG, interleukin-1β, tumor necrosis factor-α, interleukin-6 and interleukin-8 are expressed in higher proportions in the chondrocytes of OA patients [6,9].…”
Section: Discussionmentioning
confidence: 99%
“…Various cytokines such as nitric oxide, PG, interleukin-1β, tumor necrosis factor-α, interleukin-6 and interleukin-8 are expressed in higher proportions in the chondrocytes of OA patients [6,9]. Chondrocytes play an important role in the onset of pain during inflammation by activating the neurons [7,16]. Studies have demonstrated that the expressions of interleukin-4, tumor necrosis factor-α, interleukin-6, and interleukin-13 are promoted by P2X7R activation [17].…”
Section: Discussionmentioning
confidence: 99%
“…Chondrocytes lack the capacity to drive efficient repair and thus in osteoarthritis (OA) articular cartilage is irreversibly damaged. While earlier studies viewed OA as a wear-and-tear condition, there is now a consensus, reviewed by Konitten et al, 1 that chondrocytes both respond to and may themselves produce proinflammatory cytokines which can result in cartilage breakdown through modulating the expression of metalloproteinases including a disintegrin and metalloproteinase with thrombospondin domains (ADAMTS) enzymes, matrix metalloproteinases (MMPs), and serine proteinases. 2 Interplay of pain-related neurovascular peptides with cartilage biology submit your manuscript | www.dovepress.com…”
Section: The Cartilage Environmentmentioning
confidence: 99%
“…These levels remain high for weeks and even months after trauma (Catterall et al, 2010;Olson et al, 2014;Christiansen et al, 2015). Based on clinical observations, cartilage derived biomarkers increase significantly a month after knee injury (Kramer et al, 2011;Konttinen et al, 2012). This shows that significant cartilage damage takes place weeks after the trauma, hence early intervention can effectively prevent long-term articular destruction (Imamura et al, 2015).…”
Section: Introductionmentioning
confidence: 99%